2010
DOI: 10.1017/s1751731109991339
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin E and plant extract mixture composed of carvacrol, cinnamaldehyde and capsaicin on oxidative stress induced by high PUFA load in young pigs

Abstract: The objective of our study was to determine the antioxidative potential of a plant extract (PE) mixture composed of carvacrol, capsicum oleoresin and cinnamaldehyde against high n-3 polyunsaturated fatty acid (PUFA)-induced oxidative stress in young pigs. Thirty-two weaned castrated male crossbred pigs (BW 10.9 kg; n 5 32) were randomly assigned to four dietary treatments (n 5 8). The negative control diet (Cont) contained 17.2% energy from fat. Oxidative stress was induced in three of the four experimental gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 34 publications
(37 reference statements)
5
25
0
3
Order By: Relevance
“…CBO is one of the most important volatile oils. Although there is no evidence about the effect of cinnamaldehyde, which is the major component of CBO used in this study, on sperm parameters, testis structure, and sperm DNA integrity, it has been reported that ingestion of plant extract containing cinnamaldehyde effectively protects pig lymphocytes against oxidative DNA damage (51). Oil and other products of C. zeylanicum have been reported to result in decrease in testicular lipid peroxidation levels, and increases in LH, FSH, and testosterone (52,53) concentrations; reproductive organ weights; sperm count and motility; antioxidant activities (GSH, GSH-Px, and CAT); and DST in healthy animals (28).…”
Section: Beneficial Effect Of Cbomentioning
confidence: 78%
“…CBO is one of the most important volatile oils. Although there is no evidence about the effect of cinnamaldehyde, which is the major component of CBO used in this study, on sperm parameters, testis structure, and sperm DNA integrity, it has been reported that ingestion of plant extract containing cinnamaldehyde effectively protects pig lymphocytes against oxidative DNA damage (51). Oil and other products of C. zeylanicum have been reported to result in decrease in testicular lipid peroxidation levels, and increases in LH, FSH, and testosterone (52,53) concentrations; reproductive organ weights; sperm count and motility; antioxidant activities (GSH, GSH-Px, and CAT); and DST in healthy animals (28).…”
Section: Beneficial Effect Of Cbomentioning
confidence: 78%
“…Supplemental CS or CS+LMA in the diets (21 to 64 days of age) did not influence the body weight, feed intake and FCR of piglets (P>0.05). Positive effects of supplementing CS, DL-LMA or CS+LMA on growth performance and health of piglets have been observed (Kaewtapee et al 2009;Frankic et al 2010;Jarupan et al 2018). However, several reports showed that CS supplementation did not support the growth rate and feed utilization (Udompoka, 2006), and less positive response in growth performance from the supplementation of various feed additives has been also reported (Walsh et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The treatment with carvacrol restored the imbalance between ROS and antioxidant system and by the way prevented the fragmentation. 24 In conclusion, the viability of donor pancreas islets is protected with carvacrol treatment and carvacrol effectively protects of apoptosis. All of the steps were applied according to the manufacturer's instructions.…”
Section: Islet Isolation and H 2 O 2 Treatmentmentioning
confidence: 87%